Structure, function and evolution of the Archaeal class I fructose-1, 6-bisphosphate aldolase. (1st April 2004) - Lorentzen, E.; Siebers, B.; Hensel, R.; Pohl, E.
Abstract : FBPA (fructose-1, 6-bisphosphate aldolase) catalyses the reversible aldol condensation of glyceraldehyde 3-phosphate and dihydroxyacetone phosphate to form fructose 1, 6-bisphosphate. Two classes of FBPA, which rely on different reaction mechanisms, have so far been discovered, class I mainly found in Eucarya and class II mainly in Bacteria. Only recently were genes encoding proteins with FBPA activity identified in Archaea. Archaeal FBPAs do not share any significant overall sequence identity with members of the traditional classes of FBPAs, raising the interesting question of whether they have evolved independently by convergent evolution or diverged from a common ancestor. Biochemical characterization of FBPAs of the two hyperthermophilic Archaea Thermoproteus tenax and Pyrococcus furiosus showed that the enzymes use a Schiff-base mechanism and thus belong to the class I aldolases. The crystal structure of the archaeal FBPA from T. tenax revealed that the protein fold, as for the classical FBPA I and II, is that of a parallel (βα)8 barrel. A substrate-bound crystal structure allowed detailed active-site comparisons which showed the conservation of six important catalytic and substrate-binding residues between the archaeal and the classical FBPA I. This observation provides further evidence that the two sequence families of proteins share a common evolutionary origin. Furthermore, structure and sequence analysis indicate that the class I FBPA shares a common evolutionary origin with several other enzyme superfamilies of the (βα)8 barrel fold.